Graphene oxide-loaded fluorine-cerium nanoparticles as well as preparation method and application thereof
By loading fluorine cerium nanoparticles on graphene oxide, using their photothermal conversion and adsorption properties, the problem of existing photothermal technology is solved in the low efficiency of organic pollutants, and the rapid and efficient pyrolysis of organic dyes is achieved, providing a green and economical pollutant treatment method.
Patent Information
- Application Number
- CN202510016583.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, photothermal technology is inefficient in the pyrolysis process of organic pollutants, and traditional heating methods are non-green, have low cost performance and are difficult to promote.
A material supported by graphene oxide with cerium fluorine nanoparticles was designed, and prepared by ultrasonic dispersion and chemical reaction methods. The photothermal conversion ability of graphene oxide and the large-capacity adsorption performance of fluorine nanoparticles were used to achieve efficient pyrolysis of organic dyes.
It realizes rapid and efficient pyrolysis of organic dyes, improves the pyrolysis efficiency of pollutants, and provides a new idea for green and economical treatment of pollutants.
Smart Images

Figure CN119702018A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-efficiency photothermal pyrolysis materials for organic pollutants, and in particular to graphene oxide-loaded fluorinated cerium nanoparticles and a preparation method and application thereof. Background Art
[0002] After separation, organic pollutants in water bodies need to be further treated to achieve harmlessness or high value, which puts forward major technical requirements for environmental protection science and technology workers. Pyrolysis of pollutants is a traditional and effective strategy for treating solid waste pollutants, but it is limited by the non-green nature of heating methods and extremely low cost-effectiveness, which makes this type of method difficult to apply and promote (Science of The Total Environment Volume 801, 20 December 2021, 149696).
[0003] In recent years, photothermal technology has become an important green energy supply technology, and has shown great application potential in the fields of wound treatment, catalytic oxidation, etc. (Angew. Chem. Int. Ed. 2017, 56, 7842; ChemCatalysis, Volume 2, Issue 1, 52-83). Applying photothermal technology to the pyrolysis process of organic pollutants may be one of the ideal means to treat pollutants. However, photothermal conversion is a typical heat surface localization technology, which makes it difficult for organic pollutants to approach the high-temperature area formed by photogenerated heat, resulting in extremely low pyrolysis efficiency of organic pollutants. In order to improve energy utilization efficiency, functional design of materials is one of the important ideas. At present, the technology of two-dimensional material loading nanoparticles has been well explored in the field of photothermal conversion (Nanoscale, 2023, 15, 2455-2469; ChemCatalysis, Volume 1, Issue 2, 272-297). Three-dimensional ordered macroporous carbon is a new type of carbon material formed by uniformly arranged macropores (pore size above 50 nm) running through the entire material. It has great advantages in accelerating the diffusion of substances (Chemical Society Review., 2013,42, 794-830). As a typical carbon material, light irradiation can cause the π electrons inside the material to form transition and relaxation cycles, which in turn leads to the conversion of photon energy into heat energy. Therefore, three-dimensional ordered macroporous carbon is expected to become a new type of photothermal material with great potential. Acetate-based lanthanide fluoride materials are a new type of material composed of acetate layers and lanthanide fluoride single atoms arranged in an orderly manner. They have great application potential in dye adsorption (Journal of the American Chemical society. 2019, 141, 33, 13134–13142; Applied Surface Science, 2023, 621, 156842).
[0004] As a typical two-dimensional material, graphene has excellent photothermal conversion ability and has shown good application potential in related experiments (ACS Nano 2013, 7, 2, 1281–1290). In the experiment, we found that loading fluorinated cerium nanoparticles on the surface of graphene oxide can effectively enrich organic pollutants on the surface of graphene, and can make full use of the photothermal conversion ability of graphene to achieve thermal removal of organic pollutants.
[0005] In summary, it is necessary to design a graphene oxide loaded with fluorinated cerium nanoparticles for photothermal decomposition of organic pollutants, and to explore the preparation rules of this type of material, and apply it to the photothermal decomposition reaction of organic pollutants, which will have a positive impact on the advancement of sewage treatment technology and has great theoretical value and application prospects. Summary of the invention
[0006] In order to address the deficiencies in the prior art, the present invention provides a graphene oxide-loaded fluorine-cerium nanoparticle, a preparation method and application thereof. The graphene oxide-loaded fluorine-cerium nanoparticle in the present invention is a material with a novel multi-level structure. The present invention makes full use of the excellent photothermal properties of graphene oxide and the large-capacity adsorption performance of fluorine-cerium nanoparticles for organic dyes, thereby enabling the organic dye to be placed in an effective high-temperature pyrolysis area and achieving pyrolysis of pollutants.
[0007] In order to achieve the above object, the specific scheme adopted by the present invention is: On the one hand, in view of the current lack of research on photothermal conversion materials with multi-level structures, the present invention provides a method for preparing graphene oxide-loaded fluorinated cerium nanoparticles, which mainly includes the following steps: Step (1), ultrasonically dispersing the graphene oxide aqueous solution to obtain a uniform solution A; Step (2), adding cerium acetate to the uniform solution A, and continuously stirring in a water bath at a constant temperature to obtain a uniform solution B; Step (3), adding potassium fluoroborate to the uniform solution B, and continuously stirring in a water bath at a constant temperature to obtain a turbid solution; Step (4), centrifuging and freeze-drying the turbid solution after continuous stirring to obtain graphene oxide-loaded fluorinated cerium nanoparticles.
[0008] Wherein, step (1) is to make the graphene oxide powder evenly dispersed in the aqueous solution; step (2) is added to step (1) to make the cerium ions in cerium acetate evenly distributed on the surface of graphene oxide; step (3) is added to step (2) so that after potassium fluoroborate releases fluoride ions, fluoride ions, acetate ions and cerium ions react to form fluorine cerium nanoparticles; step (4) is to remove impurities and collect F-Ce@GO.
[0009] Furthermore, in step (1), the concentration of the graphene oxide aqueous solution is 0.02-0.2 mg / mL, and the volume is 10-200 mL.
[0010] Furthermore, in step (2), the amount of cerium acetate added is 0.1 to 15 g; In step (3), the amount of potassium fluoroborate added is 0.01-10 g.
[0011] Furthermore, in step (1), the ultrasonication time is 30 min; In step (2), stirring is continued at 25°C for 10 to 60 min; In step (3), stirring is continued at 25°C for 0.5 to 24 h.
[0012] On the other hand, the present invention provides a graphene oxide loaded fluorine cerium nanoparticles, which are prepared by the above method; the graphene oxide loaded fluorine cerium nanoparticles are recorded as F-Ce@GO, and the fluorine cerium nanoparticles with a size of 10 to 50 nm in F-Ce@GO are loaded on graphene oxide, and the fluorine cerium nanoparticles do not significantly affect the size and appearance of graphene oxide.
[0013] On the other hand, in view of the shortcomings of slow pyrolysis rate and low pyrolysis efficiency of existing organic dyes, the present invention provides an application of graphene oxide loaded fluorinated cerium nanoparticles in the field of photothermal pyrolysis of organic dyes to achieve efficient pyrolysis of organic dyes.
[0014] Furthermore, the photothermal decomposition of organic dyes mainly comprises the following steps: Step 1: Place F-Ce@GO in a Congo red dye solution, shake it, centrifuge it and dry it to obtain F-Ce@GO-CR adsorbed with organic dye; Step 2: Place F-Ce@GO-CR in silica aerogel and irradiate it with laser for a certain period of time. Under the action of laser, F-Ce@GO generates local high temperature, thereby causing thermal decomposition of the organic dye.
[0015] Furthermore, in step 1, the organic dye is any one of Congo red, Coomassie brilliant blue, rhodamine B, orange G, methyl orange, methyl blue, and methylene blue.
[0016] Furthermore, in step 1, the volume of the organic dye solution is 10~150 mL, the concentration is 50~2000 mg / L; the mass of F-Ce@GO is 0.10~1.00 g; and the oscillation time is 0.5 h~8 h.
[0017] Furthermore, in step 2, the mass of F-Ce@GO-CR is 0.5~10 mg, the laser wavelength is 375~1650 nm, and the laser power is 0.6~2.0 W / cm 2 , laser irradiation time is 5~300 min.
[0018] Beneficial effects: (1) The graphene oxide loaded fluorine cerium nanoparticles in the present invention is a material with a novel multi-level structure. The present invention makes full use of the excellent photothermal properties of graphene oxide and the large-capacity adsorption performance of fluorine cerium nanoparticles for organic dyes, thereby enabling the organic dyes to be placed in an effective high-temperature pyrolysis region and achieving pyrolysis of pollutants.
[0019] (2) In the process of preparing graphene oxide-loaded fluorinated cerium nanoparticles, the present invention does not need to add additional active agents or template agents, thereby avoiding the contamination of the material by the active agent and reducing the cumbersome post-processing steps of the template agent.
[0020] (3) The F-Ce@GO prepared in the present invention can achieve rapid and efficient pyrolysis of organic dyes, and is expected to provide a new idea for the pyrolysis of organic pollutants.
[0021] (4) The preparation method of this material is simple, low-cost, environmentally friendly and reusable, and is expected to show great application potential in the development of high-performance photothermal pyrolysis materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a low-magnification SEM image of F-Ce@GO prepared in Example 1.
[0023] Figure 2 This is a low-magnification TEM image of F-Ce@GO prepared in Example 1.
[0024] Figure 3 This is the UV-visible spectrum of F-Ce@GO prepared in Example 1 before and after photothermal decomposition of Congo red dye at different powers (the solvent is dimethyl sulfoxide).
[0025] Figure 4 This is the UV-visible spectrum of F-Ce@GO prepared in Example 1 before and after photothermal pyrolysis of Congo red dye at the same power for different times (the solvent is dimethyl sulfoxide).
[0026] Figure 5 This is a low-magnification SEM image of F-Ce@GO-CR prepared in Example 2 after photothermal pyrolysis.
[0027] Figure 6 This is a low-magnification SEM image of F-Ce@GO-CR prepared in Example 3 after photothermal pyrolysis.
[0028] Figure 7 This is a low-magnification SEM image of F-Ce@GO-CR prepared in Example 4 after photothermal pyrolysis. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] Example 1 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 10 mL of 0.02 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 0.5 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 5 min to obtain a homogeneous solution B; (3) Add 0.02 g potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 30 min to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) 0.1 g F-Ce@GO was placed in 20 mL 100 mg / L Congo red aqueous solution, shaken for 0.5 h, centrifuged and dried to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption amount of 563.8 mg / g; (6) Weigh 0.1 mg of F-Ce@GO-CR and place it in silica aerogel. The wavelength is 980 nm and the power density is 0.61 W / cm 2 , 0.76 W / cm 2 , 0.83 W / cm 2 , 0.90 W / cm 2 , 1.06 W / cm 2 After 5 min of laser irradiation, Figure 3 The UV-visible spectra of F-Ce@GO adsorbed Congo red dye dissolved in dimethyl sulfoxide before and after photothermal pyrolysis at different powers show that the maximum pyrolysis efficiency of the dye is 94.02%; at a power density of 0.76 W / cm 2 Expose light at different times. Figure 4 The UV-visible spectra of F-Ce@GO adsorbed Congo red dye dissolved in dimethyl sulfoxide before and after photothermal pyrolysis for different times at the same power. It can be seen that the maximum pyrolysis efficiency of the dye is 97.3%.
[0031] In step (4), the low magnification SEM image of F-Ce@GO is as follows: Figure 1 As shown, it can be observed that the overall contrast is relatively uniform, proving that the morphology and structure of graphene oxide loaded with fluorinated cerium nanoparticles have not changed significantly; Figure 2 This is a TEM image in low-magnification mode, which clearly shows that the fluorine cerium nanoparticles with large contrast (black dots in the image, with a size of about 10 nm) are evenly dispersed in the entire material without obvious aggregation. Figure 1 and Figure 2 The experimental results clearly show that the material obtained in step (4) is graphene oxide loaded with fluorinated cerium nanoparticles.
[0032] Example 2 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 50 mL of 0.05 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 1 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 20 min to obtain a homogeneous solution B; (3) Add 0.5 g potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 1 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) Place 0.5 g F-Ce@GO in 50 mL 400 mg / L Congo red aqueous solution, shake for 1 h, centrifuge and dry to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption amount of 2822.8 mg / g. (6) Weigh 2 mg of F-Ce@GO-CR and place it on silica aerogel. 2 After laser irradiation for 10 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 70.57%.
[0033] In step (6), the low magnification SEM image of F-Ce@GO-CR after illumination is as follows: Figure 5 As shown, it can be observed that the overall contrast is relatively uniform and the morphological structure has not changed significantly.
[0034] Example 3 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 20 mL of 0.1 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 3 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 30 min to obtain a homogeneous solution B; (3) Add 1 g of potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 4 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) 0.6 g F-Ce@GO was placed in 100 mL 400 mg / L Congo red aqueous solution, shaken for 2 h, centrifuged and dried to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption amount of 3390.4 mg / g; (6) Weigh 3 mg of F-Ce@GO-CR and place it on silica aerogel. 2 After laser irradiation for 30 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 84.76%.
[0035] In step (6), the low-magnification SEM photo of F-Ce@GO-CR after illumination is shown in the attached figure. Figure 6 As shown, it can be observed that the overall contrast is relatively uniform and the morphological structure has not changed significantly.
[0036] Example 4 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 50 mL of 0.13 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 5 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 45 min to obtain a homogeneous solution B; (3) Add 4 g potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 6 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) Place 1 g of F-Ce@GO in 100 mL of 800 mg / L Congo red aqueous solution, shake for 3 h, centrifuge and dry to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption amount of 7108.8 mg / g; (6) Weigh 3 mg of F-Ce@GO-CR and place it in silica aerogel. 2 After laser irradiation for 45 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 88.86%.
[0037] In step (6), the low-magnification SEM photo of F-Ce@GO-CR after illumination is shown in the attached figure. Figure 7 As shown, it can be observed that the overall contrast is relatively uniform and the morphological structure has not changed significantly.
[0038] Example 5 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 80 mL of 0.2 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 8 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 50 min to obtain a homogeneous solution B; (3) Add 6 g of potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 8 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) Place 0.3 g F-Ce@GO in 50 mL 1000 mg / L Congo red aqueous solution, shake for 4 h, centrifuge and dry to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption capacity of 9214 mg / g. (6) Weigh 5 mg of F-Ce@GO-CR and place it on silica aerogel. 2 After laser irradiation for 60 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 92.14%.
[0039] Example 6 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 60 mL of 0.2 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 10 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 60 min to obtain a homogeneous solution B; (3) Add 8 g of potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 12 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) Place 0.8 g F-Ce@GO in 10 mL 1500 mg / L Congo red aqueous solution, shake for 5 h, centrifuge and dry to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption amount of 11670 mg / g. (6) Weigh 10 mg of F-Ce@GO-CR and place it on silica aerogel. 2 After laser irradiation for 120 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 77.80%.
[0040] Example 7 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 100 mL of 0.2 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 12 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 60 min to obtain a homogeneous solution B; (3) Add 9 g of potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 16 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) Place 0.1 g F-Ce@GO in 50 mL 400 mg / L Congo red aqueous solution, shake for 6 h, centrifuge and dry to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption amount of 18590 mg / g; (6) Weigh 1 mg of F-Ce@GO-CR and place it on silica aerogel. 2 After laser irradiation for 180 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 92.95%.
[0041] Example 8 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 100 mL of 0.2 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 15 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 50 min to obtain a homogeneous solution B; (3) Add 10 g of potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 8 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) Place 0.2 g F-Ce@GO in 150 mL 2000 mg / L Congo red aqueous solution, shake for 8 h, centrifuge and dry to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption amount of 19248 mg / g; (6) Weigh 2 mg of F-Ce@GO-CR and place it in silica aerogel. 2 After laser irradiation for 240 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 96.24%.
[0042] Example 9 This embodiment provides a method for preparing and applying graphene oxide-loaded fluorinated cerium nanoparticles, which mainly comprises the following steps: (1) Ultrasonicate 80 mL of 0.2 mg / mL graphene oxide aqueous solution for 30 min to obtain a uniform solution A; (2) Add 7 g of cerium acetate to the homogeneous solution A and stir continuously in a water bath at 25°C for 50 min to obtain a homogeneous solution B; (3) Add 10 g potassium fluoroborate to the homogeneous solution B and stir continuously in a water bath at 25°C for 24 h to obtain a turbid solution. (4) The turbid solution obtained in step (3) was centrifuged at 5000 rpm, and the precipitate was collected and freeze-dried to obtain F-Ce@GO; (5) Place 0.5 g of F-Ce@GO in 80 mL of 2000 mg / L Congo red aqueous solution, shake for 0.5 h, centrifuge and dry to obtain F-Ce@GO-CR adsorbed with Congo red dye, with an adsorption capacity of 20,000 mg / g. (6) Weigh 10 mg of F-Ce@GO-CR and place it in silica aerogel. 2 After laser irradiation for 300 min, the UV-visible spectra of F-Ce@GO-CR dissolved in dimethyl sulfoxide before and after photothermal pyrolysis showed that the dye pyrolysis efficiency was 99.52%.
[0043] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing graphene oxide-loaded fluorinated cerium nanoparticles, characterized in that: The main steps are as follows: Step (1), ultrasonically dispersing the graphene oxide aqueous solution to obtain a uniform solution A; Step (2), adding cerium acetate to the uniform solution A, and continuously stirring in a water bath at a constant temperature to obtain a uniform solution B; Step (3), adding potassium fluoroborate to the uniform solution B, and continuously stirring in a water bath at a constant temperature to obtain a turbid solution; Step (4), centrifuging and freeze-drying the turbid solution to obtain graphene oxide-loaded cerium fluoride nanoparticles.
2. The method for preparing graphene oxide-supported fluorinated cerium nanoparticles according to claim 1, characterized in that: In step (1), the concentration of the graphene oxide aqueous solution is 0.02-0.2 mg / mL, and the volume is 10-200 mL.
3. The method for preparing graphene oxide-loaded fluorinated cerium nanoparticles according to claim 2, characterized in that: In step (2), the amount of cerium acetate added is 0.1-15 g; In step (3), the amount of potassium fluoroborate added is 0.01-10 g.
4. The method for preparing graphene oxide-supported fluorinated cerium nanoparticles according to claim 1, characterized in that: In step (1), the ultrasonication time is 30 min; In step (2), stirring is continued at 25°C for 10 to 60 min; In step (3), stirring is continued at 25°C for 0.5 to 24 h.
5. A graphene oxide loaded fluorine cerium nanoparticle, characterized in that: It is prepared by the method described in any one of claims 1 to 4. The graphene oxide loaded fluorine cerium nanoparticles is recorded as F-Ce@GO. In the F-Ce@GO, the fluorine cerium nanoparticles with a size of 10 to 50 nm are loaded on the surface of the graphene oxide.
6. An application of the graphene oxide-loaded cerium fluoride nanoparticles as claimed in claim 5 in the field of photothermal pyrolysis of organic dyes.
7. The use according to claim 6, characterized in that The photothermal decomposition of organic dyes mainly includes the following steps: Step 1: placing F-Ce@GO in an organic dye solution, centrifugally separating and drying after shaking to obtain F-Ce@GO-CR adsorbed with the organic dye; Step 2: Place F-Ce@GO-CR on the surface of silica aerogel and irradiate it with laser for a certain period of time. Under the action of laser, F-Ce@GO generates local high temperature, thereby causing thermal decomposition of the organic dye.
8. The use according to claim 7, characterized in that In step 1, the organic dye is any one of Congo red, Coomassie brilliant blue, rhodamine B, orange G, methyl orange, methyl blue, and methylene blue.
9. The use according to claim 7, characterized in that The volume of the organic dye solution is 10~150 mL, and the concentration is 50~2000 mg / L; the mass of F-Ce@GO is 0.10~1.00 g; and the oscillation time is 0.5 h~8 h.
10. The use according to claim 7, characterized in that In step 2, the mass of F-Ce@GO-CR is 0.5~10mg, the laser wavelength is 375~1650nm, and the laser power is 0.6~2.0 W / cm 2 , laser irradiation time is 5~300 min.